(untitled) (Global Journal of Science Frontier Research, 2019)
On the example of the gravitational and electrostatic fields, the distribution of any equipotentials in with a uniform and accelerated particle motion is analyzed. It is shown that inertia is determined by the distortion of equipotentials. It is also shown that Einstein corrections to the mass and energy of a particle at about light speeds are also determined by the distortion of the equipotentials due to the delay time of the interaction of the particle with equipotentials. Potential waves, transverse with respect to the amplitude of the potential oscillations and longitudinal with respect to the amplitude, oscillations of force, which describe "gravitational waves" without any convolutions of space-time, are incomprehensible. The conclusion is made about the general character of Newton’s laws for any potential fields, which makes it possible to combine methods of measuring gravitational and electric fields. A unified approach to the calculation of centrifugal and magnetic forces showed weakness / incompleteness of their definitions, which led to the emergence of a number of "theoretical" disasters.